The Importance of Good Customer Ethics in Improving The Financing Portion of Mudharabah - Khotibul Umam (Global Review of Islamic Economics and Business, 2016)
Mudharabah is a partnership contract (reputation agreement) in which one party (shahibul maal) will give his property to another party (mudharib) as productive business capital  with profit sharing between the owner of the funds/capital based on the agreed ratio in advance. In practice, the application of financing mudharabah is not easy to be implemented in Islamic banking because financing mudharabah will make the asymmetric information between the customer and Islamic banking. Mudharabah client have more information than Islamic banking about all of that business.  Asymmetric information sometimes can make the costumer do the moral hazard and adverse selection acts with the result that Islamic banking didn't take that risk and make the distribution of mudharabah financing portion becomes very small when compared to the total number of Islamic bank financing. Mudharabah Customers must have a good business ethics and always have advanced principle of honesty, trustworthy and transparent in managing shahibul maal funds in orther to they can minimize the risk of financing mudharabah and make Islamic banking be confident to grant the decision of financing mudharabah.